ABOUT THE FLASHES’ ACTIVITY OF AO535+26 IN OPTICAL BAND - Dorokhov, N. I.; Dorokhova, T. N.; Beletskiy, Yu. V. (Одеські астрономічні публікації, 2017)
After the great multipulse outburst of Oct. 1995 (JD 2450019) was recorded we followed the optical activity of Be/neutron star binary system A0535+26. The information on optical flares during 25 years of photoelectric observations was replenished by the photovisual observations of the 7-camera astrograph collection of Odessa Astronomical Observatory during 24 years. The particularities of each from 10 revealed flashes are given.